Disciplinary Writing Tutors at Work: A study of the Character of the Feedback Provided on Academic Writing at the BA Programmes at the Humanities Department - Christensen, Vibeke; Hobel, Peter (Journal of Academic Writing, 2020)
New students struggle to develop academic writing skills during transition to university. To meet this challenge, the Humanities department at the University of Southern Denmark implemented a research and development project to increase feedback to student writers. In the project, graduate students were trained as disciplinary writing tutors, and subsequently provided feedback on undergraduates’ assignments. The study presented in this article examines the feedback offered by the disciplinary writing tutors. As researchers, we ask, “What characterises the feedback offered by the disciplinary writing tutors?” The study is positioned in a sociocultural framework that draws on theories of disciplinary and academic literacy. Data was collected in four bachelor’s degree programmes and consists of the feedback given by the tutors and interviews with the tutors conducted at the end of the tutoring. Principal results indicate that the feedback on the students’ texts is distributed at the text layer of content and structure and the text layer of formalities. Feedback at the text layer of sentences is almost absent. Feedback on the writing and learning processes is limited. The discipline-specific feedback occurs as indications in the feedback to the BA students and is made clearer when comparing feedback in different programmes. The feedback the writing tutors provide demonstrates an understanding of academic writing as academic socialisation.